Smart Blind Stick Design Using HC-SR04 Sensor and ESP 32 Based Water Level Sensor to Improve the Mobility of Blind Persons - Zakhir, Zharfan; Maulana, Halim (Ilmu Bersama Center, 2024)
Blind people in Indonesia, who are estimated to number around 3.75 million people, face major challenges in their daily mobility. In the era of technology 4.0, various innovations have been developed to help them, including the use of walking aids such as smart blind sticks. This research aims to design and build a smart blind stick based on the ESP32 microcontroller, which is equipped with an HC-SR04 ultrasonic sensor and water level sensor to detect holes and puddles of water, as well as a vibration module and speaker to provide warnings. The research method used is the prototyping method, which involves collecting system requirements, making prototypes, and evaluating users. The research results show that this smart blind stick is effective in providing warnings of obstacles on the road through vibration and sound, as well as making travel easier and increasing the safety of blind people. All main components function as expected, making this device a practical and innovative solution for improving the mobility of blind people.